A COMPARATIVE STUDY OF LOW-DENSITY POLYETHYLENE SHOPPING CARRY BAG DEGRADING BACTERIA ISOLATED FROM MARINE AND GARDEN SOIL - Katru, Ramya Sugandhi; Ladi, Reshma; Hamzah, Husam Talib; Velluru, Sridevi; Babu, BK (International Journal of Research -GRANTHAALAYAH, 2023)
An attempt was made to investigate the extent of biodegradability of LDPE by six strains were isolated from marine and garden soil. The phenotypic fingerprint, similar to the Gen III biolog, was utilised to activate the substrate utilisation of strains, which were identified as Paenibacillus castanea and Riemerella anatipestifer. The optimal conditions for both was found to be pH of 7.1, temperature of 37oC, contact time of 72hrs, LDPE weight & inoculums volume of Paenibacillus castanea; 0.030 g & 3 % (v/v) for Riemerella anatipestifer; 0.042 g & 4% (v/v). LDPE degradation was confirmed by the weight loss which was found to be 7.30 % for Paenibacillus castanea & 5.40 % for Riemerella anatipestifer after an incubation of 35 days. The present study suggest that Paenibacillus castanea is efficient, cost effective, eco friendly and safe approach for the elimination of LDPE compared to Riemerella anatipestifer from the environment. The changes in the functional group of Paenibacillus castanea was further detected by FTIR. These results indicate that Paenibacillus castanea can prove to be a suitable candidate for LDPE treatment without causing any harm to our health or environment.